Ultra-low moisture coated carbon current collector, preparation method thereof, electrode and battery

By covering the hydrophobic ionic gel on the surface of the carbon-coated current collector and wrapping the conductive agent, the battery performance problems caused by the carbon-coated current collector are solved, and the effect of high cycle life and low inflation is achieved.

CN119695162APending Publication Date: 2025-03-25JIANGYIN NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311232016.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing carbon coated current collectors are prone to absorb water during use, resulting in increased internal resistance of the battery, reduced cycle life, and gas bloating, affecting battery performance.

Method used

By covering the hydrophobic ionic gel on the surface of the current collector, the hydrophobic ionic gel is obtained by polymerization of hydrophobic monomers in the hydrophobic ionic liquid, encapsulating the conductive agent, thereby reducing the moisture content to reach below 400PPM.

Benefits of technology

The battery capacity still reaches more than 96% after 600 cycles, reducing the battery's inflation and bloating phenomenon, and improving the battery's cycle life and performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004464252000000071
    Figure BDA0004464252000000071
  • Figure BDA0004464252000000081
    Figure BDA0004464252000000081
Patent Text Reader

Abstract

The invention provides an ultra-low moisture coated carbon current collector, a preparation method thereof, an electrode and a battery. The provided ultralow-moisture carbon-coated current collector comprises a current collector and slurry coated on the surface of the current collector, wherein the slurry comprises hydrophobic ionic gel, a conductive agent, a binder, a solvent and a wetting agent, and the hydrophobic ionic gel is obtained by polymerizing a hydrophobic monomer in hydrophobic ionic liquid; the water content in the carbon-coated current collector reaches 400 PPM or below. And the capacity of the battery prepared by applying the carbon-coated current collector can still reach 96% or above after 600 cycles, so that the swelling and swelling phenomena of the battery can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to an ultra-low moisture carbon-coated current collector and a preparation method thereof, an electrode and a battery. Background Art

[0002] Carbon-coated current collector is a current collector that can improve the contact interface between the positive and negative active materials and the foil. The matrix of the carbon-coated current collector is the current collector, on which the dispersed conductive carbon black or carbon-coated particles are coated. The carbon-coated current collector is mainly used in lithium iron phosphate power batteries, which has the advantages of increasing battery energy density, inhibiting battery polarization, reducing battery internal resistance, increasing battery cycle life, and improving battery material processing performance. In recent years, with the increase in battery energy density requirements, the market demand for carbon-coated current collectors has been continuously released. At present, nearly 90% of power lithium batteries have used carbon-coated current collectors.

[0003] Conductive agents coated on the surface of carbon-coated current collectors are usually conductive carbon black, graphite, carbon nanotubes, graphene, etc. These materials have a large specific surface area and contain polar groups on the surface, such as carboxyl and hydroxyl groups, which are easy to absorb water during use. If the water content is too high, the electrolyte and water will react to generate trace amounts of harmful gases; when there is enough water, the pressure inside the battery will increase, causing the battery to deform under stress, commonly known as "bulging"; excessive water content will deplete the effective components of the electrolyte and also deplete lithium ions, causing irreversible chemical reactions of lithium ions in the negative electrode of the battery, reducing the battery capacity.

[0004] Further improvements are needed on carbon-coated current collectors. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. The present invention provides an ultra-low moisture carbon-coated current collector and a preparation method thereof, an electrode and a battery. The moisture content in the ultra-low moisture carbon-coated current collector provided is as low as below 400 PPM, so that the capacity of the battery prepared by using the ultra-low moisture carbon-coated current collector can be ensured to be still high after multiple cycles, thereby reducing the bloating phenomenon of the battery.

[0006] Specifically, the present invention provides the following technical solutions:

[0007] The first aspect of the present invention provides an ultra-low moisture carbon-coated current collector, comprising: a current collector and a slurry coated on the surface of the current collector; wherein the slurry comprises a hydrophobic ion gel, a conductive agent, a binder, a solvent and a wetting agent, and the hydrophobic ion gel is obtained by polymerizing a hydrophobic monomer in a hydrophobic ionic liquid; the moisture content of the carbon-coated current collector reaches below 400 PPM.

[0008] The present invention creatively conceives of covering the surface of the current collector with a hydrophobic ion gel, which forms a dense hydrophobic interface on the surface of the hydrophobic ion gel. The conductive agent is wrapped by the hydrophobic ion gel, thereby isolating the conductive agent from external moisture, so that the moisture content of the provided carbon-coated current collector is very low, for example, reaching below 400 PPM. The battery prepared by using the ultra-low moisture carbon-coated current collector provided by the present invention can still reach more than 96% capacity after 600 cycles, thereby reducing the bloating phenomenon of the battery.

[0009] According to an embodiment of the present invention, the ultra-low moisture carbon-coated current collector described above may further include the following technical features:

[0010] According to an embodiment of the present invention, the hydrophobic monomer is tert-butyl acrylate, and the hydrophobic ionic liquid is 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt. Using tert-butyl acrylate as the hydrophobic monomer and 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt as the hydrophobic ionic liquid, the prepared hydrophobic ion gel has a fully hydrophobic structure compared to other types of hydrophobic ion gels, and the preparation process is simple and efficient, and the obtained hydrophobic ion gel has strong hydrophobicity.

[0011] The mass ratio of the hydrophobic monomer and the hydrophobic ionic liquid is within a suitable range, and a hydrophobic ion gel with strong hydrophobicity and excellent performance can be obtained through polymerization reaction. When the content of the hydrophobic monomer is too high or too low, the polymerization reaction efficiency will be reduced, the reaction speed will be too fast, or the relative molecular weight of the product will be difficult to control. In addition, too low or too high will affect the performance parameters of the gel, thereby affecting the hydrophobicity of the hydrophobic ion gel. According to an embodiment of the present invention, the mass ratio of the hydrophobic monomer and the hydrophobic ionic liquid is (1-2): (5-15), preferably 2: (5-10), for example, 2: 8.

[0012] According to an embodiment of the present invention, the mass ratio of the hydrophobic ion gel to the conductive agent is (2-7): (8-10), for example (2.5-5): (8.5-9.5). The carbon-coated current collector prepared in this way has a very low moisture content, a low resistance, and good overall performance.

[0013] According to an embodiment of the present invention, the polymerization reaction temperature is 50-60 degrees Celsius and the pressure is 0.3-0.8 MPa.

[0014] According to an embodiment of the present invention, the conductive agent is selected from at least one of conductive carbon black, graphite carbon, nanotubes, and graphene. According to a preferred embodiment, the conductive agent is a mixed conductive agent, that is, at least two conductive agents, such as a mixture of two, three, or four conductive agents. By using a mixed conductive agent, a variety of conductive agent shapes can provide more conductive networks inside it, thereby reducing the film resistance of the prepared carbon-coated current collector.

[0015] According to an embodiment of the present invention, the adhesive is a polyacrylic acid type adhesive.

[0016] According to an embodiment of the present invention, the solvent is pure water.

[0017] According to an embodiment of the present invention, the wetting agent is selected from at least one of polyether silicone and alcohol substances.

[0018] The second aspect of the present invention provides a method for preparing an ultra-low moisture carbon-coated current collector, comprising:

[0019] (1) polymerizing a hydrophobic monomer in a hydrophobic ionic liquid to form a hydrophobic ion gel;

[0020] (2) kneading and coating the hydrophobic ion gel and the conductive agent so that the hydrophobic ion gel coats the surface of the conductive agent to obtain a material;

[0021] (3) mixing the material obtained in step (2) with a binder, a solvent, and a wetting agent, and stirring to obtain a slurry;

[0022] (4) The slurry of step (3) is coated on a current collector to obtain an ultra-low moisture carbon-coated current collector.

[0023] By polymerizing hydrophobic monomers in a hydrophobic ionic liquid, a hydrophobic ion gel with significant hydrophobic effect can be obtained, and the preparation method of the hydrophobic ion gel is relatively simple and efficient; the hydrophobic ion gel and the conductive agent are kneaded and coated, and the kneading process can make the solid conductive agent and the hydrophobic ion gel stir to produce a coating layer, so that the hydrophobic ion gel wraps the surface of the conductive agent; and further mixed and stirred with a binder, a solvent, and a wetting agent, and the formed slurry is coated on the collector to prepare a carbon-coated collector with a moisture content as low as 400PPM or less.

[0024] According to an embodiment of the present invention, the method described above may further include the following technical features:

[0025] According to an embodiment of the present invention, the hydrophobic ion gel in step (1) is prepared by the following method:

[0026] The hydrophobic monomer is polymerized in a hydrophobic ionic liquid, the polymerization reaction temperature is 50 to 60 degrees Celsius, and the pressure is 0.3 to 0.8 MPa.

[0027] According to an embodiment of the present invention, in step (2), a dough mixer is used to knead and coat the hydrophobic ion gel and the conductive agent, and the stirring speed of the dough mixer is 20 to 100 rpm, and the stirring time is 0.3 to 1 hour. By using the dough mixer for bonding and coating, the hydrophobic ion gel can be fully coated on the surface of the conductive agent. According to a preferred embodiment, the stirring speed of the dough mixer is 30 rpm, and the stirring time is 0.5 hour.

[0028] According to an embodiment of the present invention, the stirring speed of the mixing of the material and the binder, solvent and wetting agent in step (3) is 20 to 60 rpm, and the dispersion speed is 1500 to 3000 rpm. For example, the stirring speed is 20 to 60 rpm, and the dispersion speed is 2000 rpm.

[0029] According to an embodiment of the present invention, the coating rate in step (4) is 30-120 m / min, and after coating, the coating is dried at 60-100 degrees Celsius.

[0030] A third aspect of the present invention provides an electrode, comprising the carbon-coated current collector according to the first aspect, wherein an active layer is disposed on at least one side of the surface of the carbon-coated current collector.

[0031] A fourth aspect of the present invention provides a battery, comprising the electrode described in the third aspect.

[0032] The beneficial effects achieved by the present invention are:

[0033] 1. The battery prepared by the ultra-low moisture carbon-coated current collector provided by the present invention was cycled 600 times, and the capacity reached more than 96%, reducing the battery's bloating phenomenon.

[0034] 2. The method for preparing the ultra-low moisture carbon-coated current collector mentioned in the present invention is simple, efficient and convenient for industrial application. DETAILED DESCRIPTION

[0035] Embodiments of the present invention are described in detail below. The described embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.

[0036] The present invention provides an ultra-low moisture carbon-coated current collector, comprising:

[0037] A current collector and a slurry coated on the surface of the current collector; wherein the slurry includes a hydrophobic ion gel, a conductive agent, a binder, a solvent and a wetting agent, and the hydrophobic ion gel is obtained by polymerizing a hydrophobic monomer in a hydrophobic ionic liquid; the water content in the carbon-coated current collector reaches below 400 PPM, or even reaches below 200 PPM.

[0038] The carbon-coated current collector provided by the present invention creatively covers the surface of the current collector with a hydrophobic ion gel, and the hydrophobic ion gel wraps the conductive agent, and a dense hydrophobic interface is formed on the surface of the hydrophobic ion gel, thereby isolating the external moisture from the conductive agent, so that the moisture content of the carbon-coated current collector provided by the present invention is very low. The battery prepared by the ultra-low moisture carbon-coated current collector provided by the present invention has a capacity of more than 96% after 600 cycles, reducing the bloating phenomenon of the battery.

[0039] According to a specific embodiment, the hydrophobic monomer is tert-butyl acrylate, and the hydrophobic ionic liquid is 1-butyl-3-methylimidazolium bis trifluoromethanesulfonyl imide salt. Tert-butyl acrylate is an extremely important chemical basic raw material and intermediate. Because it has a unique and highly active polar molecule, unsaturated double bond and carboxylate (-COOR) structure, it can derive many polymer formulas with good performance, and prepare plastic, cross-linked polymers through emulsion polymerization, solution polymerization, copolymerization and other processing methods. The present invention uses the polymerization of hydrophobic monomer (tert-butyl acrylate) in hydrophobic ionic liquid (1-butyl-3-methylimidazolium bis trifluoromethanesulfonyl imide salt), and the polymerization reaction conditions are temperature 50-60 ° C, pressure 0.5Mpa, and the mass ratio of hydrophobic monomer to hydrophobic ionic liquid is 2:8 to form a hydrophobic ion gel. The hydrophobic polymer network on the surface of the gel aggregates under the hydrophobic effect to form a dense hydrophobic interface, thereby effectively blocking the cross-interface diffusion of water molecules.

[0040] According to a specific embodiment, the conductive agent is selected from at least one of conductive carbon black, graphite carbon, nanotubes, and graphene. The conductive agent is kneaded and coated with a hydrophobic ion gel using a combination of one or more of conductive carbon black, graphite carbon, nanotubes, and graphene. According to a specific embodiment, the conductive agent is selected from at least two, at least three, or at least four of conductive carbon black, graphite carbon, nanotubes, and graphene.

[0041] The hydrophobic ion gel wraps the surface of the conductive agent. After the material is formed, the material and other adhesives, solvents, and wetting agents are added to a double planetary stirring tank in a certain proportion to prepare a coating slurry. The stirring speed is 30 revolutions per minute. The dispersion speed is 2000 revolutions per minute. The stirring and dispersion time of the homogenized slurry is two hours. Thus, the slurry can be coated on the surface of the current collector to obtain an ultra-low moisture carbon-coated current collector.

[0042] According to an embodiment of the present invention, the adhesive is a polyacrylic acid type adhesive.

[0043] According to an embodiment of the present invention, the solvent is pure water.

[0044] According to an embodiment of the present invention, the wetting agent is selected from at least one of polyether silicone and alcohol substances.

[0045] The present invention also provides a method for preparing the ultra-low moisture carbon-coated current collector, comprising:

[0046] (1) polymerizing a hydrophobic monomer in a hydrophobic ionic liquid to form a hydrophobic ion gel;

[0047] (2) kneading and coating the hydrophobic ion gel and the conductive agent so that the hydrophobic ion gel coats the surface of the conductive agent to form a material;

[0048] (3) mixing the material obtained in step (2) with a binder, a solvent, and a wetting agent, and stirring to obtain a slurry;

[0049] (4) The slurry of step (3) is coated on a current collector to obtain an ultra-low moisture carbon-coated current collector.

[0050] By polymerizing hydrophobic monomers in a hydrophobic ionic liquid, a hydrophobic ion gel with significant hydrophobic effect can be obtained, and the preparation method of the hydrophobic ion gel is relatively simple and efficient; the hydrophobic ion gel and the conductive agent are kneaded and coated, and the kneading process can make the solid conductive agent and the hydrophobic ion gel stir to produce a coating layer, so that the hydrophobic ion gel wraps the surface of the conductive agent; and further mixed and stirred with a binder, a solvent, and a wetting agent, and the formed slurry is coated on the collector to prepare a carbon-coated collector with a moisture content as low as 400PPM or less.

[0051] According to a specific implementation manner, in step (2), a dough mixer is used to knead and coat the hydrophobic ion gel and the conductive agent. A certain amount of hydrophobic ion gel and conductive agent are added into the dough mixer. Stirring and coating are performed for a certain period of time, so that the ion gel fully surrounds the surface of the conductive agent. If a conventional agitator is used, the conventional dispersion disk will break the coating film coated with the gel, which is not conducive to forming a coating on the surface of the conductive agent, so a dough mixer is used for kneading and coating, which has a better effect. According to a specific implementation manner, the process parameters during the kneading and coating process are stirring speed: 30 rpm, time 0.5 hours.

[0052] The material prepared in step (2) and other adhesives, solvents, and wetting agents are added to a double planetary stirring tank in a certain proportion to prepare a coating slurry. The stirring speed is 30 revolutions per minute. The dispersion speed is 2000 revolutions per minute. The stirring and dispersion time of the homogenate is about two hours. According to a specific embodiment, the adhesive used is a polyacrylic acid type adhesive. The solvent is pure water, and the wetting agent is polyether silicone, alcohols, and other substances.

[0053] According to the specific implementation, the slurry can be coated on both sides of the current collector. The coating method can be gravure roller coating, dip coating, narrow slit extrusion, spray coating, etc. A double-sided coating one-time molding machine is used to improve production efficiency. The coating speed range is: 30-120m / min, and the drying temperature of the oven is 60-100℃.

[0054] The present invention further provides an electrode, comprising the carbon-coated current collector described above or the carbon-coated current collector prepared by the above method, wherein an active layer is disposed on at least one side of the surface of the carbon-coated current collector.

[0055] The present invention also provides a battery, comprising the electrode described above.

[0056] According to a specific embodiment, the ultra-low moisture carbon-coated current collector is prepared by the following method:

[0057] S1 Preparation of hydrophobic ion gel: tert-butyl acrylate is an extremely important basic chemical raw material and intermediate. Because of its unique and highly active polar molecules, unsaturated double bonds and carboxylate (-COOR) structure, it can be derived into many polymer formulas with good performance, and plastic, cross-linked polymers are prepared through emulsion polymerization, solution polymerization, copolymerization and other processing methods. This patent uses the polymerization of hydrophobic monomers (tert-butyl acrylate) in hydrophobic ionic liquids (1-butyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt). The polymerization reaction conditions are a temperature of 50-60°C, a pressure of 0.5Mpa, and a mass ratio of monomer to ionic liquid of 2:8 to form a hydrophobic ion gel. The hydrophobic polymer network on the surface of the gel aggregates under the hydrophobic effect to form a dense hydrophobic interface, which can effectively block the cross-interface diffusion of water molecules.

[0058] S2 hydrophobic ion gel and conductive agent are kneaded and coated: the conductive agent of the carbon-coated current collector is generally a combination of one or more conductive carbon black, graphite carbon, nanotubes, graphene, etc.

[0059] S3 homogenization to prepare slurry: the materials prepared in step S2 and other adhesives, solvents, and wetting agents are added to a double planetary stirring tank in a certain proportion to prepare a coating slurry. The stirring speed is 30 revolutions per minute. The dispersion speed is 2000 revolutions per minute. The stirring and dispersion time of the homogenization is two hours. The adhesive of this patent adopts a polyacrylic acid type adhesive. The solvent is pure water, and the wetting agent is polyether silicone, alcohols and other substances.

[0060] S4 current collector processing coating: Apply the slurry configured in S3 on both sides of the current collector. The coating method can be gravure roller coating, dip coating, narrow slit extrusion, spraying, etc. A double-sided coating one-time molding machine is used to improve production efficiency. Coating speed range: 30-120m / min, oven drying temperature 60-100℃.

[0061] The technical solution of the present invention is described below by means of specific embodiments. It should be noted that these embodiments are only used to help those skilled in the art understand the present invention and should not be regarded as limiting the scope of protection of the present invention.

[0062] Example 1

[0063] Example 1 provides a carbon-coated current collector, which is prepared by the following method:

[0064] (1) polymerizing a hydrophobic monomer, tert-butyl acrylate, in a hydrophobic ionic liquid, 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt, to form a hydrophobic ion gel, wherein the mass ratio of the two is 2:8; wherein the polymerization reaction temperature is 55 degrees Celsius and the pressure is 0.5 MPa;

[0065] (2) kneading and coating 2.5 kg of hydrophobic ion gel and 9 kg of conductive carbon black with a dough mixer, so that the hydrophobic ion gel coats the surface of the conductive agent, wherein the corresponding process parameters are a stirring speed of 30 rpm and a time of 0.5 hour;

[0066] (3) The material obtained in step (2), 24 kg of a binder, 150 kg of a solvent (water), and 0.5 kg of a wetting agent are added to a double planetary stirring tank to prepare a slurry. The stirring speed is 30 revolutions per minute. The dispersion speed is 2000 revolutions per minute, and the stirring and dispersion time of the slurry is two hours. The binder used is polyvinyl alcohol (PVA); and the wetting agent is sodium dodecyl sulfate.

[0067] (4) Using a double-sided coating one-step forming machine, the slurry of step (3) is sprayed on both sides of the current collector at a coating speed of 80 m / min to obtain a carbon-coated current collector.

[0068] Example 2

[0069] Example 2: A carbon-coated current collector is prepared by referring to the method of Example 1. The difference between Example 2 and Example 1 is that the amount of hydrophobic ion gel used is 4.5 kg, as shown in Table 1.

[0070] Example 3

[0071] Example 3: A carbon-coated current collector was prepared by referring to the method of Example 1. The difference between Example 3 and Example 1 is that the amount of hydrophobic ion gel used is 6.5 kg, as shown in Table 1.

[0072] Example 4

[0073] Example 4: A carbon-coated current collector is prepared by referring to the method of Example 1. The difference between Example 4 and Example 1 is that the conductive agent used is a mixed conductive agent, that is, 4.5 kg of conductive carbon black and 4.5 kg of graphite are mixed.

[0074] Example 5

[0075] Example 5: A carbon-coated current collector is prepared by referring to the method of Example 1. The difference between Example 5 and Example 1 is that the conductive agent used is a mixed conductive agent, that is, 3 kg of conductive carbon black, 3 kg of graphite and 3 kg of graphene are mixed.

[0076] Comparative Example 1

[0077] Comparative Example 1 A carbon-coated current collector was prepared by referring to the method of Example 1. The difference between Comparative Example 1 and Example 1 is that the hydrophobic ion gel is not contained.

[0078] Comparative Example 2

[0079] Comparative Example 2: A carbon-coated current collector is prepared by the method of Reference Example 1. The difference between Comparative Example 2 and Example 1 is that the mass ratio of the hydrophobic monomer tert-butyl acrylate and the hydrophobic ionic liquid 1-butyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt is 1:20, and 1.2 kg of the hydrophobic ion gel and 9 kg of the conductive agent conductive carbon black are kneaded and coated.

[0080] Comparative Example 3

[0081] Comparative Example 3: A carbon-coated current collector is prepared by the method of Reference Example 1. The difference between Comparative Example 3 and Example 1 is that the mass ratio of the hydrophobic monomer tert-butyl acrylate and the hydrophobic ionic liquid 1-butyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt is 1:2, and 12 kg of the hydrophobic ion gel and 9 kg of the conductive agent conductive carbon black are kneaded and coated.

[0082] Table 1 Data of various embodiments and comparative examples

[0083]

[0084]

[0085] The carbon-coated current collectors prepared in the examples and comparative examples were subjected to moisture measurement and film resistance measurement using methods commonly used in the art, such as using a film resistance meter to measure the film resistance.

[0086] Table 2 Experimental results

[0087] Moisture(PPM) Film resistance (mΩ) Example 1 400 130 Example 2 200 140 Example 3 200 180 Example 4 200 125 Example 5 200 100 Comparative Example 1 1200 100 Comparative Example 2 700 126 Comparative Example 3 400 200

[0088] From the above results, it can be seen that in Comparative Example 1, no hydrophobic ion gel is added, and the water content of the carbon-coated current collector prepared is very high, reaching 1200PPM, and the membrane resistance is low, which is 100 milliohms. In Comparative Example 2, the content of hydrophobic ionic liquid is too high compared to the content of hydrophobic monomer, and the content of hydrophobic ion gel is too low compared to the content of conductive agent. Although the membrane resistance value is not high, the water content of the prepared carbon-coated current collector is very high. In Comparative Example 3, because the content of hydrophobic monomer is too high compared to the content of hydrophobic ionic liquid, and the content of hydrophobic ion gel is too high compared to the content of conductive agent, the water content of the prepared carbon-coated current collector reaches 400PPM, but the membrane resistance is high, reaching 200mΩ.

[0089] Comparing the results of Examples 1, 2, and 3, it is not difficult to see that the variables of Examples 1, 2, and 3 are to increase the amount of hydrophobic ion gel used at a certain gradient. It can be seen that as the amount of hydrophobic ion gel added increases, the moisture content of the prepared carbon-coated current collector is gradually decreasing, but when the amount reaches 4.5 kg, its moisture content no longer continues to decrease. Moreover, with the addition of hydrophobic ion gel, the membrane resistance of the prepared carbon-coated current collector continues to increase. Based on Examples 1, 2, and 3, the optimal amount of hydrophobic ion gel added is 4.5 kg.

[0090] The difference between Example 4 and Example 5 is that the conductive agent adopts a mixed formula. Example 4 is a mixture of conductive carbon black and graphite. Example 5 is a combination of conductive carbon black, graphite and graphene. It can be seen from Example 4 and Example 5 that as the type of conductive agent used increases, the diaphragm resistance decreases. Not limited by theory, one reason is that the various shapes of the conductive agent provide more conductive networks inside it, which reduces the diaphragm resistance. The battery prepared by Example 1 to Example 5 was cycled 600 times, and the capacity was still able to reach more than 96%.

[0091] Generally speaking, if the water content of the product in the battery is lower than 800PPM, the battery will not have side reactions, bulging, flatulence and other abnormal conditions. It is not difficult to see from the results of the above Examples 1 to 5 that, because of the addition of the hydrophobic ion gel, even if the highest water content is 400PPM, and some even reach 200PPM, the membrane resistance is not high, and the contribution to the battery is very large. At the same time, the hydrophobic ion gel allows the passage of this ion and does not have a great impact on the resistance of the carbon-coated current collector.

[0092] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.

[0093] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. An ultra-low moisture carbon-coated current collector, characterized in that: It includes a current collector and a slurry coated on the surface of the current collector; The slurry comprises a hydrophobic ion gel, a conductive agent, a binder, a solvent and a wetting agent, wherein the hydrophobic ion gel is obtained by polymerization of a hydrophobic monomer in a hydrophobic ionic liquid; The water content in the carbon-coated current collector is below 400 PPM.

2. The ultra-low moisture carbon-coated current collector according to claim 1, characterized in that: The hydrophobic monomer is tert-butyl acrylate, and the hydrophobic ionic liquid is 1-butyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide salt; The mass ratio of the hydrophobic monomer to the hydrophobic ionic liquid is (1-2):(5-15).

3. The ultra-low moisture carbon-coated current collector according to claim 1, characterized in that: The mass ratio of the hydrophobic ion gel to the conductive agent is (2-7):(8-10).

4. The ultra-low moisture carbon-coated current collector according to claim 1, characterized in that: The polymerization reaction is carried out at a temperature of 50 to 60 degrees Celsius and a pressure of 0.3 to 0.8 MPa.

5. The ultra-low moisture carbon-coated current collector according to claim 1, characterized in that: The conductive agent is selected from at least one of conductive carbon black, graphite carbon, nanotubes, and graphene; The adhesive is a polyacrylic acid type adhesive; The solvent is water; The wetting agent is selected from at least one of polyether silicone and alcohol substances.

6. A method for preparing an ultra-low moisture carbon-coated current collector, characterized in that: include: (1) polymerizing a hydrophobic monomer in a hydrophobic ionic liquid to form a hydrophobic ion gel; (2) kneading and coating the hydrophobic ion gel and the conductive agent so that the hydrophobic ion gel coats the surface of the conductive agent to obtain a material; (3) mixing the material obtained in step (2) with a binder, a solvent, and a wetting agent, and stirring to obtain a slurry; (4) The slurry of step (3) is coated on a current collector to obtain an ultra-low moisture carbon-coated current collector.

7. The method according to claim 6, characterized in that In step (2), a dough mixer is used to knead and coat the hydrophobic ion gel and the conductive agent. The stirring speed of the dough mixer is 20 to 100 rpm, and the stirring time is 0.3 to 1 hour.

8. The method according to claim 6, characterized in that In step (3), the stirring speed of the material and the binder, solvent and wetting agent is 20 to 60 revolutions per minute, and the dispersion speed is 1500 to 3000 revolutions per minute; The coating speed in step (4) is 30-120 m / min, and after coating, the coating is dried at 60-100 degrees Celsius.

9. An electrode, characterized in that: The electrode comprises the carbon-coated current collector according to any one of claims 1 to 5, and an active layer is disposed on at least one side of the surface of the carbon-coated current collector.

10. A battery, characterized in that: The battery comprises the electrode according to claim 9.

Citation Information

Patent Citations

  • Water system primary coating current collector for lithium ion battery, and preparation method and application of current collector

    CN106784857A

  • Carbon-coated aluminum foil for lithium ion batteries

    CN109935837A